Gestão da educação superior a distância no Brasil na perspectiva dos atos normativos - Andrade, Pollyana Vieira de (2022)
This dissertation has as its theme the management of distance higher education in Brazil, from the perspective of normative acts, developed in the Graduate Program in Education of the Faculty of Education, Federal University of Goiás (UFG), in the research line State, Politics and History of Education. The general objective is to analyze the management of distance higher education, established in specific legal frameworks of the federal government for distance education. This is a bibliographic, qualitative and descriptive research, of documentary nature, which, besides collecting documents on distance higher education, analyzes the normative perspective related to its management. For the theoretical basis of this research, the studies of Chauí (2001, 2003), Dourado (2008, 2011, 2020), Dias Sobrinho (2005, 2008, 2018), Sguissardi (2014, 2015, 2020), Franco (2021), Sousa (2021), Azevedo and Catani (2020), Dalberio (2009), Leher (2019), Belloni (1999, 2002), Costa (2010, 2013), Lima, D. (2013, 2021), Cury (2000, 2002, 2011), Sander (2005), Franco and Morosini (2005), Libâneo, Oliveira and Toschi (2012), Momo and Behr (2015), Mill, Ferreira, M. and Ferreira, D. (2018), Mill and Santiago (2021), Alonso (2010), Dourado, Santos and Moraes (2017), Dourado and Oliveira (2009), Dourado, Moraes and Ribeiro (2020), Maieski, Alonso and Anjos (2020), Behr and Costa (2014), among others. The research was developed based on the study model developed by Momo and Behr (2015) and, thus, in the researched realities about the management of higher education at a distance in Brazil, from the perspective of normative acts linked to the modality, it was verified the administrative, structural and teaching-learning process management. It was found that the administrative and structural managements deal with aspects related to expansionist and market issues of DE, showing the intense process of flexibilization of the modality in course. In relation to the management of the teaching-learning process, it was found that the normative acts deal with aspects related to training, however, it was observed flexibilities regarding the rules for monitoring the process in question, which may interfere with the quality of the courses offered. It was understood, therefore, that for an efficient EaD management in public higher education institutions, these three management perspectives should be understood as integrative and complementary. However, beyond the legislation that configures the forms of delivery and organization of DE, the importance of treating the actions related to its management as a fundamental issue for the incorporation and development of the modality in institutional practices was noted. However, in a context of strong influence of the neoliberal state, it was possible to observe that the normative acts studied reveal that public institutions of higher education have been developing their management actions as a social organization and not as a social institution. In this context favorable to contradictions, it was also verified that education, as a social right and public good, disputes space with education as business and merchandise, marked by a "field of dispute" (BOURDIEU, 2004) and contemplating what is called "Operational University" (CHAUÍ, 2003). It was verified, therefore, that it is in this scenario that we find the distance education modality (DE) in public institutions of higher education. It is believed, finally, in a distance education built on a critical-socially-referenced basis.